2021
DOI: 10.1101/2021.11.19.21266601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence and widespread circulation of a recombinant SARS-CoV-2 lineage in North America

Abstract: Genetic recombination is an important driving force of coronavirus evolution. While some degree of virus recombination has been reported during the COVID-19 pandemic, previously detected recombinant lineages of SARS-CoV-2 have shown limited circulation and been observed only in restricted areas. Prompted by reports of unusual genetic similarities among several Pango lineages detected mainly in North and Central America, we present a detailed phylogenetic analysis of four SARS-CoV-2 lineages (B.1.627, B.1.628, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…The level, scale and consequences of recombination during the pandemic are unclear; one earlier study of phylogenetic inconsistency found no clear signals of recombination 93 , whereas a more recent analysis of UK sequence data discovered at least four groups of natural recombinants of B.1.1.7 and other parental lineages 94 . The increasing co-circulation in 2021 of genetically diverse viruses increases the likelihood that further SARS-CoV-2 recombinants will be detected 95 .…”
Section: Homoplasy and Recombinationmentioning
confidence: 99%
“…The level, scale and consequences of recombination during the pandemic are unclear; one earlier study of phylogenetic inconsistency found no clear signals of recombination 93 , whereas a more recent analysis of UK sequence data discovered at least four groups of natural recombinants of B.1.1.7 and other parental lineages 94 . The increasing co-circulation in 2021 of genetically diverse viruses increases the likelihood that further SARS-CoV-2 recombinants will be detected 95 .…”
Section: Homoplasy and Recombinationmentioning
confidence: 99%
“…New reports supporting evidence of recombination events have started emerging, including evidence of recombination between B.1.1.7 and B.1.177 lineages and evidence supporting the recombining origins of lineage B.1.628 ( 51 ). More recently, a group reported the first case of an intra-host recombination event during a co-infection with Delta and Gamma of the sample in the study ( 52 ). This is the first reporting of a recombination event during co-infection of an individual.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported the detection of SARS-CoV-2 recombinant lineages circulating at a low frequency ( 11 , 12 , 18 21 ). Nevertheless, these studies were restricted to detecting the inter-host dissemination of genomes post-recombination events, which could be biased by spurious mutations generated due to library preparation, laboratory contamination, and unavailability of raw sequenced data.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this phenomenon occurs at a relatively high frequency among betacoronaviruses ( 8 10 ). In SARS-CoV-2, signals of ongoing recombination were observed in a few sequences deposited in GISAID and circulating in North America ( 11 , 12 ). Both studies showed evidence of recombination between non-variants of concern.…”
Section: Introductionmentioning
confidence: 99%